Evaluation of Selenium and Vitamin E Levels in Women with Recurrent Miscarriage - Zeina J. AbduLshaheed; Ali A. H. Albakaa; Hasan Abd Ali Khudhair (University of Thi-Qar Journal of Science, 2023)
The most frequent pregnancy issue is a miscarriage, which is defined as the spontaneous end of pregnancy before the fetus reaches viability. The current research aims to identify the potential significance of selenium (Se) and vitamin E (VE) as predictive diagnostic biomarkers in recurrent pregnancy loss (RPL). Methods: A case control study that included three study groups; 35 women with RPL, 30 non-aborted pregnant (NAP) women, and 25 healthy women. After rigorously applying the eligibility requirements, patients were chosen from those visiting Bint Al-Huda Teaching Hospital and Suq Al-Shuyukh General Hospital in Thi-Qar Province (Iraq). Serum VE and serum Se levels were determined using the ELISA and atomic absorption spectrophotometer techniques, respectively. Results: The outcomes showed that the RPL group’s serum VE and Se below normal levels were (88.6% and 62.9% respectively) lower than in the healthy control group (28% and 24% respectively). The level of VE was depleted in NAP group (93.3%) compared to HC group (28%) with significant differences, whereas the level of Se was significantly lower in RPL group (62.9%) compared NAP group (13.3%). Conclusions: A significant positive association of VE and Se in RPL and a significant negative association of VE and Se in NAP and HC.